Peran Gereja Dalam Pemberantasan Korupsi Di Indonesia Korelasi Dengan Mikha 7:3 - Ekoprodjo, 1Herman Sjahthi; Wibowo, Markus (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2024)
Corruption is a major problem that undermines the social, economic and moral order in Indonesia. The church, as a religious institution, has an important role to play in the fight against corruption by promoting moral and ethical values based on the teachings of the Bible. This article discusses the role of the church in the fight against corruption, highlighting the correlation between the principles taught in Micah 7:3 and the concrete actions that the church can take. The church can play a role through moral education, advocacy, co-operation with anti-corruption agencies, the establishment of anti-corruption communities, and spiritual support. With this approach, the church is expected to be able to form individuals with integrity and encourage the creation of a more just and transparent society.